2021
DOI: 10.30996/persona.v10i1.4986
|View full text |Cite
|
Sign up to set email alerts
|

Adaptasi dan uji properti psikometrik The PERMA-Profiler pada orang Indonesia

Abstract: The PERMA-Profiler is a well-being instrument which combines the hedonic and eudaimonic perspective of well-being. This instrument was developed based on well-being theory (Seligman, 2012) which explained well-being as a multidimensional construct, included positive emotion, engagement, relationship, meaning, and accomplishment (PERMA). This study aimed to adapt and examine the psychometric properties of the PERMA-Profiler in Indonesian people. The participants were 439 Indonesians, aged 17-63 years old (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Flourishing was measured using the PERMA Profiler subscale of Butler and Kern (2016) which was later adapted by Elfida et al (2021) for an Indonesian sample. Fifteen items were used in this study, divided into three items per dimension which were positive emotions, engagement, relationships, meaning, and accomplishments.…”
Section: Data Collection Techniquementioning
confidence: 99%
“…Flourishing was measured using the PERMA Profiler subscale of Butler and Kern (2016) which was later adapted by Elfida et al (2021) for an Indonesian sample. Fifteen items were used in this study, divided into three items per dimension which were positive emotions, engagement, relationships, meaning, and accomplishments.…”
Section: Data Collection Techniquementioning
confidence: 99%
“…3 skala yaitu skala kebahagiaan otentik, skala penerimaan diri dan skala dukungan sosial. Pengukuran kebahagiaan otentik dilakukan dengan menggunakan skala The Perma Profiler yang mengacu pada Well Being Theory serta sudah diadaptasi dan diterjemahkan (Elfida et al, 2021). Skala Penerimaan Diri diadaptasi dari Ryff Psychological Well Being yang telah diterjemahkan ke dalam bahasa Indonesia.…”
Section: Instrumen Penelitianunclassified
“…However, Butler and Kern (2016) have designed a scale named PERMA Profiler, which allows the measuring of flourishing by operationalizing the five proposed pillars. It is worth mentioning that the scale has been translated and adapted in different countries, finding a greater number of adaptations for the adult population (Cobo-Rendón et al, 2020;de Carvalho, 2021;Demirci et al, 2017;Elfida et al, 2021;Giangrasso, 2021;Pezirkianidis et al, 2019) than for the adolescent one (Singh & Raina, 2020). Likewise, although there are studies where the five pillars of flourishing have not been identified (Ryan et al, 2019), the replication of the factorial structure of the original scale stands out in the available adaptations (Cobo-Rendón et al, 2020;Elfida et al, 2021;Giangrasso, 2021;Pezirkianidis et al, 2019;Wammerl et al, 2019;Watanabe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the scale has been translated and adapted in different countries, finding a greater number of adaptations for the adult population (Cobo-Rendón et al, 2020;de Carvalho, 2021;Demirci et al, 2017;Elfida et al, 2021;Giangrasso, 2021;Pezirkianidis et al, 2019) than for the adolescent one (Singh & Raina, 2020). Likewise, although there are studies where the five pillars of flourishing have not been identified (Ryan et al, 2019), the replication of the factorial structure of the original scale stands out in the available adaptations (Cobo-Rendón et al, 2020;Elfida et al, 2021;Giangrasso, 2021;Pezirkianidis et al, 2019;Wammerl et al, 2019;Watanabe et al, 2018). It should be noted that in most cases, a clear and consistent structure is reported, although some authors report difficulties concerning the reliability of the engagement subscale (Bartholomaeus, et al, 2020;Pezirkianidis et al, 2019;Ryan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%